Spatial transcriptomics reveals substantial heterogeneity in triple-negative breast cancer with potential clinical implications - Xiaoxiao Wang; David Venet; Frédéric Lifrange; Denis Larsimont; Mattia Rediti; Linnea Stenbeck; Floriane Dupont; Ghizlane Rouas; Andrea Joaquin Garcia; Ligia Craciun; Laurence Buisseret; Michail Ignatiadis; et al. (Nature Communications)
Abstract While triple-negative breast cancer (TNBC) is known to be heterogeneous at the genomic and transcriptomic levels, spatial information on tumor organization and cell composition is still lacking. Here, we investigate TNBC tumor architecture including its microenvironment using spatial transcriptomics on a series of 92 patients. We perform an in-depth characterization of tumor and stroma organization and composition using an integrative approach combining histomorphological and spatial transcriptomics. Furthermore, a detailed molecular characterization of tertiary lymphoid structures leads to identify a gene signature strongly associated to disease outcome and response to immunotherapy in several tumor types beyond TNBC. A stepwise clustering analysis identifies nine TNBC spatial archetypes, further validated in external datasets. Several spatial archetypes are associated with disease outcome and characterized by potentially actionable features. In this work, we provide a comprehensive insight into the complexity of TNBC ecosystem with potential clinical relevance, opening avenues for treatment tailoring including immunotherapy.